Q: What is D X?

Write your answer...

Submit

Still have questions?

Related questions

2 x 3 x 5 x d x d x d x d x d = 30d5

2 x 3 x 5 x d x d x d x d x d = 30d5

4d x d x d = 4d3

Well for one you cant buy Alex Rider the Gemini Project because it doesn't exist what your after is Alex Rider Point Blanc and as for that you can buy it in many places like amazon or got to the libary and get it :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :D :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :p :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :o :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :b :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :x :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :) :)

Show that sec'x = d/dx (sec x) = sec x tan x. First, take note that sec x = 1/cos x; d sin x = cos x dx; d cos x = -sin x dx; and d log u = du/u. From the last, we have du = u d log u. Then, letting u = sec x, we have, d sec x = sec x d log sec x; and d log sec x = d log ( 1 / cos x ) = -d log cos x = d ( -cos x ) / cos x = sin x dx / cos x = tan x dx. Thence, d sec x = sec x tan x dx, and sec' x = sec x tan x, which is what we set out to show.

Assuming you mean what is the value of the derivative d/dx(a²x), then: d/dx(a²x) = a² The derivative (with respect to x) of d/dx(a²x) = d/dx(d/dx(a²x)) = d/dx(a²) = 0.

d/dx(uv)=u*dv/dx+v*du/dxd/dx(secxtanx)=secx*[d/dx(tanx)]+tanx*[d/dx(secx)]-The derivative of tanx is:d/dx(tan u)=[sec(u)]2*d/dx(u)d/dx(tan x)=[sec(x)]2*d/dx(x)d/dx(tan x)=[sec(x)]2*(1)d/dx(tan x)=(sec(x))2=sec2(x)-The derivative of secx is:d/dx(sec u)=[sec(u)tan(u)]*d/dx(u)d/dx(sec x)=[sec(x)tan(x)]*d/dx(x)d/dx(sec x)=[sec(x)tan(x)]*(1)d/dx(sec x)=sec(x)tan(x)d/dx(secxtanx)=secx*[sec2(x)]+tanx*[sec(x)tan(x)]d/dx(secxtanx)=sec3(x)+sec(x)tan2(x)

The answer is: L = pi x (D + d)/2 + 2 x ( C x Cos(a) + a x (D-d)/2) where a = arcsin(D-d)/(2 x C) in radians. Where C is the center distance, D is the large pulley diameter, and d is the small pulley diameter.

d=3c

d/dx [f(x) + g(x)] = d/dx [f(x)] + d/dx [g(x)] or f'(x) + g'(x) when x = 3, d/dx [f(x) + g(x)] = f'(3) + g'(3) = 1.1 + 7 = 8.1 d/dx [f(x)*g(x)] = f(x)*d/dx[g(x)] + d/dx[f(x)]*g(x) when x = 3, d/dx [f(x)*g(x)] = f(3)*g'(3) + f'(3)*g(3) = 5*7 + 1.1*(-4) = 35 - 4.4 = 31.1

d/dx (1-x)=d/dx (1)-d/dx(x)=0-1=-1

You should apply the chain rule d/dx(x.sin x) = x * d/dx(sin x) + sin x * d/dx(x) = x * cos x + sin x * 1 = x.cos x + sin x